ALTERNATIF DALAM PENYELESAIAN SENGKETA (LITIGASI DAN NON LITIGASI) - Rosita Rosita (Al-Bayyinah, 2017)
AbstractThere are two ways to settle a dispute: a) litigation, the process of settling a dispute through court system. The dispute settlement by litigation will follow legal procedures in a court, b) non-litigation, dispute settlement out of court system, for example, through negotiation, mediation, arbitration, conciliation, and settlement mediated by kepala desa (village leader) based on local customary law. Each way has its own particular advantages. A settlement through litigation is final, binding, and forcing the litigants to obey the implementation of a verdict. Therefore, an execution is provided as a forcing institution. Meanwhile, a non-litigation system settles disputes in a faster way, financially more efficient, and the verdict may variously be adapted to a broad agreement.Kata Kunci: Penyelesaian sengketa, litigasi, dan non litigasi